التحليل المكاني للمواقع الأثرية ودورها في تطوير السياحة في مدينة بغداد - Hamdan, Sawsan Sabih (Al-Adab Journal, 2015)
Often described tourism as a spatial phenomenon related to the travel of rights from one place to another, so it becomes the subject of spatial analysis is the basis from which the majority of tourist analyzes, and features the majority of the big cities with a capacity size of its services recreational and advanced infrastructure, so are attractions for many foreign tourist groups from Besides its territory, which at the same time cities exporter tourist groups seeking tranquility and recreational activities, regions and cities and other areas, and this explains the movement of domestic tourism. This study addresses one of the most important tourist activities namely archaeological tourism or historical, is the city of Baghdad from the cities that feature dimension and historical depth of civilization, embraces its shores are many historical places and archaeological buildings were, and still bear witness to the time periods experienced by the city, which could have attract large numbers of tourists as if they were rehabilitated and opened for tourism activity, and the provision of infrastructure and tourist facilities that serve this aspect, but what ails these places of neglect spontaneous or induced, the city has lost an important source of income